Prevalence of BRCA1 and BRCA2 Mutations in Unselected Breast Cancer Patients from Medellín, Colombia (2014)
ABSTRACT: Background: Approximately 5% of all breast cancers can be attributed to a mutation in the BRCA1 or BRCA2 gene. The genetic component of breast cancer in Colombia has been, for the most part, studied on cases from the Bogota region. Five different founder mutations have been identified in two studies of breast cancer patients in the Bogota region. It is important that the frequency of mutations be established among unselected cases of breast cancer of other regions of Colombia in order to estimate the genetic burden of this cancer in Colombia and to plan genetic services. The aim of this study was to establish the mutation frequencies of the BRCA genes in breast cancer patients unselected for family history or age, from Medellin, Colombia. Methods: We enrolled 280 unselected women with breast cancer from a large public hospital in Medellin, Colombia. A detailed family history from each patient and a blood sample was obtained and processed for DNA analysis. Mutations in BRCA1 and BRCA2 were sought using a combination of techniques including a panel of recurrent Hispanic BRCA mutations which consists of fifty BRCA1 mutations and forty-six BRCA2 mutations, including the five recurrent Colombian BRCA mutations. All mutations were confirmed by direct sequencing. Results: Genetic testing was successfully completed for 244 of the 280 cases (87%). Among the 244 cases, three deleterious mutations were identified (two in BRCA1 and one in BRCA2), representing 1.2% of the total. The average age of breast cancer in the mutation-positive cases was 34 years. The two BRCA1 mutations were known founder mutations (3450del4 in exon 11 and A1708E in exon 18). The BRCA2 mutation was in exon 11 (5844del5) and has not been previously reported in individuals of Colombian descent. Among the three mutation-positive families was a breast cancer family and two families with no history of breast or ovarian cancer. Conclusion: The frequency of BRCA mutations in unselected breast cancer cases from the Medellin region of Colombia is low and is approximately 1.2%. Keywords: Colombia, Breast cancer, Hereditary, BRCA1, BRCA2